(3CSFdI GdafGQi hCLhHI hdOg YfgGs - (3eMeO Hf MeRI GdafGQj, TeS GdOjf ,J (B834 (3g` s
(3ChdgG (B:s
(3eG jUQa fMh HjGf eYGfjg HOjY dZI GdcdGe ai eWGdY GdUMGFa hCMSf eG jSQai MOjK GdeUbY HJaSjQ CUhdg ai GdWhGdM hGdehGba s
(3BNQgG (B:s
(3hCQLh ef dWag Cf dG jaVMfi jhe GdJfGO Ydi QDhS GdCTgGO hGdMeO ddg Ydi fYeg GdJi jYLQ Yf EMUGFgG cd YGO s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqdas
Keywords: (3GdeLGejYs